2019
DOI: 10.1038/s41598-019-52386-0
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively spliced isoforms reveal a novel type of PTB domain in CCM2 protein

Abstract: Cerebral cavernous malformations (CCMs) is a microvascular disorder in the central nervous system. Despite tremendous efforts, the causal genetic mutation in some CCM patients has not be identified, raising the possibility of an unknown CCM locus. The CCM2/MGC4607 gene has been identified as one of three known genes causing CCMs. In this report, we defined a total of 29 novel exons and 4 novel promoters in CCM2 genomic structure and subsequently identified a total of 50 new alternative spliced isoforms of CCM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 52 publications
3
62
0
Order By: Relevance
“…The relative expression of the CCM1 gene in homogenous cell populations from selected cell lines was also examined by qPCR (5). We found that compared to other cell lines, there was a much higher relative RNA expression level of the CCM1 gene in all cancer cell lines (5) and likewise, the same phenomena were also observed in the relative RNA expression levels of CCM2 isoforms (11). These data lead us to propose a potential role of the CSC in tumorigenesis in various tissues (5,11).…”
Section: Altered Transcription Expression Of Ccm2 Isoforms In Tumorigmentioning
confidence: 72%
See 4 more Smart Citations
“…The relative expression of the CCM1 gene in homogenous cell populations from selected cell lines was also examined by qPCR (5). We found that compared to other cell lines, there was a much higher relative RNA expression level of the CCM1 gene in all cancer cell lines (5) and likewise, the same phenomena were also observed in the relative RNA expression levels of CCM2 isoforms (11). These data lead us to propose a potential role of the CSC in tumorigenesis in various tissues (5,11).…”
Section: Altered Transcription Expression Of Ccm2 Isoforms In Tumorigmentioning
confidence: 72%
“…Expression of CCM genes at both the transcriptional and translational levels was confirmed through both qPCR and western blot analysis. Allele-specific real-time quantitative PCR (qPCR) assays were designed using boundary-spanning primer sets as previously described (11) and applied to quantify the RNA levels of the endogenously expressed CCM2 isoforms using Power SYBR Green Master Mix with ViiA 7 Real-Time PCR aystem (Applied Biosystems). TissueScan™ Real-Time PCR panels (HMRT100, 103, CSRT502) with Human β-actin control primer set (Origene) were used to determine the endogenous expression levels of CCM2 isoforms among the different tissues at the transcriptional level.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations